The changing pattern of miliary tuberculosis. Issue 2 (March 1970) - Jacques, J.; Sloan, J. M.
Abstract : Over the past 20 years there has been a striking change in the clinical pattern of miliary tuberculosis, which is now more common in adults than in children. This is shown by a comparative study of the necropsy records of such cases seen in the same group of hospitals in the years 1946-9 and 1966-9. In the early period miliary tuberculosis occurred in 1·7% of necropsies, 54% of patients being under 20 years of age and suffering from a classical form of miliary tuberculosis. By 1966-9 the incidence had fallen to 0·47% of necropsies, but now all the patients seen were over 30 years of age, the majority having a `cryptic' clinical presentation. The percentage of patients diagnosed during life fell dramatically between the two periods and in the latter period most cases were only diagnosed at necropsy. While the incidence of childhood miliary tuberculosis has been reduced, it is now important to consider this diagnosis in adults with a variety of non-specific symptoms.